Estudo da produção de biodiesel etílico com óleo residual de castanha do Brasil via catálise ácida e indução por micro-ondas - Priebe, Jonas Miguel (2015)
This paper presents the data of some parameters governing ethyl biodiesel production reactions via homogeneous catalysis acid [sulfuric acid 3% (V / VTOTAL)] using nut oil from Brazil. To this was measured behavior of the concentrations of the catalyst, water and ethanol in the liquid phase system and temperature measurements in both phases volumetric flow of the volatile components condensed and the resulting rate of conversion. These reactions were carried out using heating by microwave irradiation under a frequency of 2.45 GHz single mode reactor, varying the power incited to meet variations in relationships power/mass 1.00 to 2.25 W/g being applied for reasons molars oil/ethanol 1:6, 1:12, 1:30. According to a study, it was found that the stoichiometric ratio 1: 6 was the one, which showed the most pronounced values in the volumetric flow parameters, temperatures of the liquid and vapor phases of water concentration and degradation of the acid and reducing the alcoholic component in liquid medium. However, the proportion 1:30 was the one with the highest conversion rates when compared to the same relations power/weight applied.